Against those who are unwilling to confess that the Holy Virgin is Theotokos - Cyril, Saint, Patriarch of Alexandria, approximately 370-444.; Dragas, George Dion. (Rollinsford, N.H. : Orthodox Research Institute, 2004)
The term Theotokos helped to establish the truth that Jesus Christ, who was born of the Virgin Mary, was the preexisting Son of God who also became man without ceasing to be God in order to recapitulate in Himself the entire humanity and work out an eternal salvation for it. The point here is that Jesus Christ is the same Son of God who as true God "was born" ineffably and eternally from the Father and as true man was born in time and according to the flesh from the Virgin for the completion of the ages. Jesus Christ is one person who unites in Himself two natures, the divine and the human, and thus deifies the human by leading it to participate in the perfections of the divine. The term Theotokos brings out all these aspects of the mystery of the Incarnation and stresses its soteriological import. The present text can be described as a model of Patristic theological discourse. It is an anti-heretical treatise, which refers to a central dogma of Christian theology, the doctrine of Christ.
Includes bibliographical references and indexes.
Greek text and English translation on facing pages.
Keywords: Mary, -- Blessed Virgin, Saint -- History of doctrines -- Early church, ca. 30-600.; Mary, -- Blessed Virgin, Saint -- Motherhood; Jesus Christ -- Natures -- History of doctrines -- Early church, ca. 30-600.; Incarnation -- History of doctrines -- Early church, ca. 30-600.